An FeSx doped three-dimensional covalent organic framework for degradation of dyes. (27th February 2023) - Song, Jialong; Yu, Chengyang; Liu, Yaozu; Ren, Junxia; Liu, Jianchuan; Wang, Zitao; Zhu, Liangkui; Fu, Jing; Tang, Bin; Qiu, Shilun; Wang, Yujie; Fang, Qianrong
Abstract : Here, we reported a three-dimensional mesoporous COF loaded with FeS x nanoparticles, termed JUC-598@FeS x, which can rapidly degrade dyes in the Fenton reaction. Abstract : Fenton reactions are one of the most progressive advanced oxidation processes (AOPs), which have been widely employed in industrial sewage treatment and pollutant control. Here we report a three-dimensional covalent organic framework (3D COF) with an stp net, termed JUC-598, which has a high specific surface area (∼1900 m 2 g −1 ) and interconnected hierarchical pores (micropores of ∼1.26 nm and mesopores of ∼3.62 nm). Furthermore, we chose a solvothermal method to encapsulate FeS x nanoparticles into this COF (named JUC-598@FeS x ) as Fenton catalysts. Due to well-defined hierarchical pores, JUC-598 can load the iron-compound nanoparticles to achieve nanoscale confinement and efficient dispersion for performance enhancement. Transmission electron microscopy (TEM) and corresponding energy dispersive spectroscopy (EDS) mapping analysis revealed that the encapsulation and dispersion of FeS x nanoparticles (3–4 nm) in JUC-598 were successfully realized. The JUC-598@FeS x as catalyst was used for Fenton reactions, and the results suggested that JUC-598@FeS x displayed excellent catalytic degradation efficiency, which is 95% towards crystal violet (CV) and 91% for methylene blue (MB) in 90 min, respectively. Additionally, JUC-598@FeS x can be separated from the reaction system by centrifugation and reused at least three times with a slight change of catalytic activity. This work thus promotes the promising application of COF materials in environmental treatment.